Economic Growth Of Manufacturing Companies: Long-Term Debt, Pre-Tax Foreign Income, And Earning Management - Sitoresmi, Mumpuni Wahyudiarti; Nugraheni, Agustina Prativi (ISAS, 2023)
The objective of this research is to find evidence of Long-Term Debt, Pre-Tax Foreign Income, and Earnings Management on Economic Growth. The data used are manufacturing companies listed on the Indonesia Stock Exchange from 2015-2018. This study's sample was selected using purposive sampling criteria and 12 manufacturing companies. This study uses a panel regression model with the Eviews version 10. This study found that the variable of Long-Term Debt (LTD) has a positive effect, Pre-Tax Foreign Income (PRTX), and Earnings Management (EM) have no effect on Economic Growth (EP). Research contribution gives academics, financial statement users, and regulatory bodies additional literature that Long-Term Debt (LTD) is a component that has a positive impact on Economic Growth (EP).Keywords: Long Term Debt, Pre-Tax Foreign Income, Earnings Management, Economic Growth